2012
DOI: 10.1038/pr.2012.90
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized perfluorocarbon improves gas exchange and pulmonary mechanics in preterm lambs with severe respiratory distress syndrome

Abstract: Background: aerosolized perfluorocarbon (PFc) has been proposed as an alternative method of PFc administration; however, the efficacy of aerosolized PFc in a preterm animal model has not yet been demonstrated. Methods: Twelve preterm lambs were randomized to two groups: a perfluorodecalin (PFD) aerosol group (n = 6) receiving 10 ml/kg/h of PFD delivered by an intratracheal inhalation catheter followed by 4 h of mechanical ventilation (MV) or the control group, in which animals (n = 6) were managed for 6 h with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…For instance, a standard porcine surfactant dose (200 mg/kg) for a 1,500 g infant could be delivered in just 10 minutes in contrast to the longer aerosolization times previously reported in the literature [7], [15], [28]. In the case of PFCs, recognizing that the ideal dose for aerosol delivery may vary depending on the PFC type [20], [23], [29], a dose of 10 ml/kg could be delivered to the same infant in just 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a standard porcine surfactant dose (200 mg/kg) for a 1,500 g infant could be delivered in just 10 minutes in contrast to the longer aerosolization times previously reported in the literature [7], [15], [28]. In the case of PFCs, recognizing that the ideal dose for aerosol delivery may vary depending on the PFC type [20], [23], [29], a dose of 10 ml/kg could be delivered to the same infant in just 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol delivery of surfactant and PFC has been proposed as an alternative to their intratracheal instillation for the treatment of various pulmonary diseases, including neonatal RDS [9], [12], [20], [23], [33]. The main goal of aerosol therapy with surfactant and PFC for the treatment of this syndrome would be to administer these compounds during non-invasive ventilation with minimal airway manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comparative study was carried out using 14 premature Latxa lambs delivered at 133 d of gestation (term = 145 d), it having been shown that there is severe pulmonary SF deficiency in lambs of this breed at this gestational age (29,30). Mean body weight of the lambs at birth was 3.1 ± 0.4 kg.…”
Section: Methodsmentioning
confidence: 99%
“…These animals also received 200 mg/kg of poractant alfa continuously aerosolized (during inspiration) over a period of 20 min (n = 7), delivered intratracheally by means of inhalation catheters (AeroProbe; Trudell Medical, London, Ontario, Canada) connected to a pneumatic compressor (LABneb*CCS; Trudell Medical) (30). This aerosol system can deliver up to 0.4 ml of SF per min during mechanical ventilation, with 80% of the particles having a diameter of <5 µm (21,31).…”
Section: Experimental Designmentioning
confidence: 99%